Seneca De otio 2. The Pursuit of Otium and the Vestals’ Exemplary Life - Gazzarri, Tommaso (Lucius Annaeus Seneca, 2024)
In the second chapter of Ot., Seneca endeavors to reassure his reader that he is not abandoning the core precepts of the Stoic school. To do so, he proposes a structured analysis of his stance, which — he announces — is going to be divided in two parts. This paper analyzes the illustrations and rhetorical organization of these subdivisions. It delves into Seneca’s literary and philosophical models to then offer a new reading of the closing image whereby Seneca associates the ideal of otium cum dignitate with the final duties of an old Vestal.